Platelet mass index, systemic immune-inflammation index, and neutrophil-lymphocyte ratio as practical markers in childhood brucellosis - Hilal Koyuncu; Ayşe Tolunay Oflu; Ayşe Güngör; Ayşegül Bükülmez (Revista Paulista de Pediatria)
ABSTRACT Objective: Brucellosis is a multisystem infectious disease and may cause an increase in acute phase reactants. This study aimed to examine the platelet mass index (PMI), the neutrophil-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII) in children with brucellosis and to determine their roles in focal involvement. Methods: This retrospective observational study included 69 patients with brucellosis and a control group of 69 healthy children. Inflammation markers, PMI, NLR, and SII were compared in brucellosis patients and the control group and in brucellosis patients with and without focal involvement. Results: Hemoglobin and platelet values were significantly lower in brucellosis cases compared to the control group (p<0.001), and C-reactive protein and ferritin were significantly higher (p<0.001). SII and PMI were significantly lower in the brucellosis patient group compared to the control group (p<0.001). In the comparing cases with and without focal involvement, no statistically significant difference was detected in hematological parameters and inflammation markers. Conclusions: This study showed that PMI, one of the new markers that can be calculated from complete blood count, may be useful in diagnosing childhood brucellosis. Similar results could not be reached for NLR and SII. New studies testing the diagnostic value of PMI, NLR, and SII in childhood brucellosis are needed.